Negotiating the Right to Information: Citizen–Government Interactions in the Implementation of the Regulations on Open Government Information in China. Issue 1 (2nd January 2021) - Lu, Yiyi
Abstract: This essay analyses the implementation of China's Regulations on Open Government Information (ROGI), an important piece of legislation that establishes Chinese citizens' right to information. By international standards, the ROGI only offers relatively weak protection for this right, but Chinese citizens and civil society organisations have used the ROGI creatively to pursue a variety of goals from private rights protection to public interest advocacy. Strong civic activism has been a major driving force behind the gradual progress in public access to government information that has been achieved since the ROGI came into effect in 2008.